Predicting future customer requirements for product planning - Ko, Hao Sheng. (2012)
Product planning is an essential phase in the product development cycle. To ensure the success of a product, companies must understand what types of customer requirements need to be presented in the product. Traditionally, the analysis of customer requirement importance rating is done using the Quality Function Deployment (QFD) approach. However it is soon realized that such analysis are only static while the importance of each product attribute veritably varies with time. Thus, forecasting of customer requirements provide a potential solution for companies which want to be ahead of time.